Look for Strengthening the Competitiveness of Tradition-al Snacks-Based SMEs - Tri - Widiastuti (Politeknik Negeri Bengkalis, 2020)
This study aims to analyze the competitiveness of the traditional snack home industry in the traditional snack village in Mlatibaru, Semarang. The research method was qualitative through structured interview data collection techniques. The subjects in this study were policymakers and the number of home industry players in the traditional snack village in Mlatibaru, Semarang. The data validity test includes credibility test (internal validity), source triangulation (checking data from various sources in various ways, at various times), and using reference materials, namely supporters to prove the data that the researcher has found, such as interview data, photos, and recordings. The results show that traditional snack SMEs must prepare several strategies to compete with other business actors. Strengthening competitiveness through HR improvement strategies, product efficiency, marketing, and business bookkeeping.